The initial break-up of Pangæa elicited by Late Palæozoic deglaciation - Yeh, Meng-Wan; Shellnutt, J. Gregory (Scientific reports, 2016)
The break-up of Pangæa was principally facilitated by tensional plate stress acting on pre-existing suture zones. The rifting of Pangæa began during the Early Permian along the southern Tethys margin and produced the lenticular-shaped continent known as Cimmeria. A mantle-plume model is ascribed to explain the rift-related volcanism but the NW-SE oriented Cimmerian rifts do not correlate well with pre-existing suture zones or ‘structural heterogeneities’ but appear to have a pertinent spatial and temporal association with Late Palæozoic glacial-interglacial cycles. Mantle potential temperature estimates of Cimmerian rift-related basalts (1410 °C ± 50 °C) are similar to ambient mantle conditions rather than an active mantle-plume rift as previously suggested. Moreover, we find that the distribution of glacial deposits shows significant temporal and spatial concurrence between the glacial retreat margins and rifting sites. We conclude that the location and timing of Cimmerian rifting resulted from the exploitation of structural heterogeneities within the crust that formed due to repeated glacial-interglacial cycles during the Late Palæozoic. Such effects of continental deglaciation helped to create the lenticular shape of Cimmeria and Neotethys Ocean suggesting that, in some instances, climate change may directly influence the location of rifting.